Arabian Seawater Temperature Fluctuations in the Twentieth Century - Hussain, M.A.; Abbas, Shaheen; Ansari, M.R.K. (Journal of Basic & Applied Sciences, 2012)
It is well known that in the twentieth century anthropogenic activities have changed the climatic natural variability to some extent, which resulted in statistically significant increase in the global average temperature. Global warming has increased both atmospheric and sea-surface temperatures around the world. To study the seawater temperature fluctuations in the Arabian sea, this communication performs linear trend analysis of Arabian seawater monthly average temperature data (1871-2009) obtained from Hadley British Climate Centre, UK. The warming trends (positive for every month) of average seawater temperature data show that the ocean has gained heat from the atmosphere over the last 150 years. The trend analysis also shows that the ocean rate of heat absorption in the first half of the twentieth century is higher as compared to the second half. It is clear from the trend values that the winter warming rate is higher than the summer warming rate. It has also been shown that the Karachi urban monthly maximum temperature trends are, more or less, similar to the twentieth century Arabian monthly average seawater temperature fluctuation trends. Its decadal trend values are, more or less, ten times higher than the sea surface temperature trend values.